Pemetrexed plus platinum with or without pembrolizumab in patients with previously untreated metastatic nonsquamous NSCLC: protocol-specified final analysis from KEYNOTE-189 - Rodríguez-Abreu, Delvys; Bischoff, Helge (Annals of oncology, 2021)
Background - In the phase III KEYNOTE-189 study (NCT02578680), pembrolizumab plus pemetrexed and platinum-based chemotherapy (pemetrexed-platinum) significantly improved overall survival (OS) and progression-free survival (PFS) in patients with previously untreated metastatic nonsquamous non-small-cell lung cancer (NSCLC) versus placebo plus pemetrexed-platinum. We report updated efficacy outcomes from the protocol-specified final analysis, including outcomes in patients who crossed over to pembrolizumab from pemetrexed-platinum and in patients who completed 35 cycles (∼2 years) of pembrolizumab. - Patients and methods - Eligible patients were randomized 2 : 1 to receive pembrolizumab 200 mg (n = 410) or placebo (n = 206) every 3 weeks (for up to 35 cycles, ∼2 years) plus four cycles of pemetrexed (500 mg/m2) and investigators’ choice of cisplatin (75 mg/m2) or carboplatin (area under the curve 5 mg·min/ml) every 3 weeks, followed by pemetrexed until progression. Patients assigned to placebo plus pemetrexed-platinum could cross over to pembrolizumab upon progression if eligibility criteria were met. The primary endpoints were OS and PFS. - Results - After a median follow-up of 31.0 months, pembrolizumab plus pemetrexed-platinum continued to improve OS [hazard ratio (HR), 0.56; 95% confidence interval (CI), 0.46-0.69] and PFS (HR, 0.49; 95% CI, 0.41-0.59) over placebo plus pemetrexed-platinum regardless of programmed death-ligand 1 expression. Objective response rate (ORR) (48.3% versus 19.9%) and time to second/subsequent tumor progression on next-line treatment (PFS2; HR, 0.50; 95% CI, 0.41-0.61) were improved in patients who received pembrolizumab plus pemetrexed-platinum. Eighty-four patients (40.8%) from the placebo plus pemetrexed-platinum group crossed over to pembrolizumab on-study. Grade 3-5 adverse events occurred in 72.1% of patients receiving pembrolizumab plus pemetrexed-platinum and 66.8% of patients receiving placebo plus pemetrexed-platinum. Fifty-six patients completed 35 cycles (∼2 years) of pembrolizumab; ORR was 85.7% and 53 (94.6%) were alive at data cut-off. - Conclusions - Pembrolizumab plus pemetrexed-platinum continued to show improved efficacy outcomes compared with placebo plus pemetrexed-platinum, with manageable toxicity. These findings support first-line pembrolizumab plus pemetrexed-platinum in patients with previously untreated metastatic nonsquamous NSCLC.